KEKERASAN DALAM RUMAH TANGGA DALAM HUBUNGANNYA DENGAN NILAI-NILAI BUDAYA DI SUMATERA SELATAN - Antasari, Rr. Rina (Jurnal Studi Gender Indonesia, 2013)
Domestic Violence is a universal phenomenon. The problem can be considered as a special issue since theperpetrators and the victims are relatives or are related in other forms ofÂ  legal relation. Indonesia actually hashad a anti Domestic Violence law that is the Law Number 23 Year 2004 on the Elimination ofÂ  DomesticViolence. Ideally, this law is expected to solve the problems of domestic violence in Indonesia including SouthSumatra. Unfortunately, the lawâs implementation is still not effective and this is due to a variety ofÂ  factorsbut mainly is the narrowed cultural values of the society. Meanwhile, the ideal concept of the cultural valuesthat grow in the community is that they can function as the supporting instrument towards the enforcementofÂ  the state law. In this case, deep and thorough observation on South Sumatran society shows that,consisting ofÂ  many tribes where each has each culture, the culture serves as a regulator ofÂ  the peopleâs lifeincluding household problems. Unfortunately, the are potentials of the cultural values contributing to theoccurrence ofÂ  domestic violence. On the other hand, the very same culture also provides the solutions. As aconsequence, the law number 23 of 2004 regarding the elimination on domestic violence has not beenoptimally enofrced and implemented.